Modeling mechanical behaviors of composites with various ratios of matrix–inclusion properties using movable cellular automaton method; Defence Technology; Vol. 11, iss. 1 - Smolin A. Yu. Alexey Yurievich; Shilko E. V. Evgeny Viktorovich; Astafurov S. V. Sergey Vladimirovich; Konovalenko I. S. Ivan Sergeevich; Buyakova S. P. Svetlana Petrovna; Psakhie S. G. Sergey Grigorievich (2015, 2015)
Title screen